Anatomical and histological analysis of the scalene triangle in a Japanese population: implications for thoracic outlet syndrome diagnosis and management - Toshiya Nito; Hiroshi Satake; Masahiro Tsuchiya; Naomi Hanaka; Michiaki Takagi (BMC Musculoskeletal Disorders)
Abstract Background Thoracic outlet syndrome (TOS) arises from compression of neurovascular structures within the scalene triangle, costoclavicular space, or pectoralis minor insertion. In Western populations, the average scalene triangle base width is 10.7 mm; however, corresponding anatomical data for Japanese individuals are lacking, and the association between triangle dimensions and body size remains unclear. Methods This study assessed 42 Japanese cadavers (21 males, 21 females) to measure the scalene triangle base width, transverse anterior scalene muscle insertion width, and clavicle length using a sliding caliper (Model No. 19976; Shinwa Measures, Japan). The scalene triangle was defined as the space between the anterior scalene muscle, the middle scalene muscle, and the first rib. Muscle insertions were histologically evaluated using hematoxylin-eosin, Elastica-Masson, and Safranin O staining after formalin fixation and paraffin embedding. Statistical analysis was performed with EZR (version 4.0.2). Results The average base width of the scalene triangle was 8.2 mm, which was narrower than that reported in Western populations. Males had significantly wider triangle bases and longer clavicles than did females (p < 0.01). A positive correlation was found between the base width and clavicle length (r = 0.45, p < 0.01), suggesting that body size may influence the dimensions of the scalene triangle. In larger individuals, however, an increase in triangle size may be offset by proportionally larger nerves and vessels, potentially maintaining similar spatial crowding. Histologically, the anterior scalene muscle consistently inserted onto the superior, posterior, and inferior surfaces of the first rib and was adjacent to the parietal pleura. Conversely, the middle scalene muscle is inserted only onto the superior surface of the first rib. No fibrocartilage was observed at either insertion site, indicating a fibrous enthesis. Conclusions This study presents the first detailed anatomical and histological analysis of the scalene triangle in Japanese individuals, revealing wider base widths in cadavers than those reported in Japanese TOS patients undergoing endoscopic surgery. This discrepancy suggests a possible link between triangle narrowing and TOS pathogenesis, with implications for diagnosis and treatment strategies. Additionally, the proximity of the anterior scalene muscle to the parietal pleura may increase the risk of pleural injury during surgery in this region. Clinical trial registration Not applicable.